Un parcours collectif autour du militantisme politique en Argentine : de la mémoire des « combattants révolutionnaires » aux discours sur la victimisation - Paula Sombra (Conserveries Mémorielles)
The Armed Forces Peronists (FAP) were originally a Peronist political-military organization established in the province of Buenos Aires (Argentina) in 1967. Despite known debate on the theme of memory in the Argentine public space, the FAP have always remained silent while its members – almost all of them currently pursuing their political commitment – often show few distance with their past as activists. How to understand and address the experience of ex-FAP members? How can we understand activism memory?This article examines two specific aspects underlying the development work of the memory of the recent past activism in Argentine. The first is the continuity of political experiences troughout time while the second engages the policies of forgiveness and the process of personal (and national) memorial reconstruction in countries that have suffered major collective traumas.This paper pays particular attention to a variety of ideological formulations, practices and collective values that structure the FAP and, over the years, have progressively defined the boundaries of a given experience and meaning to actions, so as to ensure the sustainability of political commitment. The analysis is founded on the certainty that interpretative keys to understand the experience of revolutionary fighters are to be found in the discourse of victimization.